Aplikasi Cadangan Produk Penjagaan Kulit - Azmi, Nur Syafiqa; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2021)
Skincare Product Recommendation Application is an application that recommend one brand of facial skincare products, namely Safi which is available in drugstores. The purpose of developing this application is to solve the users problem in identifying skincare products that are actually suit for their skin type and problem. In addition, this application also aims to guide users in the routine of facial skincare products. Therefore, the Skincare Product Recommendation Application uses the Decision Suppot System method to diagnose the type and problem of the skin of the user before recommending the skincare product to the user. The Skincare Product Recommendation application is designed based on an object-oriented approach. The methodology used to develop this application is the Rapid Application Development (RAD). The application is developed on the Windows platform using Android Studio programming tool software, Java programming as a programming language, SQLite database, and even Microsoft Windows 10 operating system. Therefore, this application can recommend skin care products. The app can also guide users to improve the recovery of the user's facial skin by providing easy personal access and trusted skincare products.